IP Telephony Applicability in Cloud Computing - Francisco Palacios; Mitchell Vásquez Bermúdez; Fausto Orozco; Diana Espinoza Villón (Journal of Science and Research, 2018)
This paper carries out a research related to the applicability of VoIP over Cloud Computing to guarantee service stability and elasticity of the organizations. In this paper, Elastix is used as an open source software that allows the management and control of a Private Branch Exchange (PBX); and for developing, it is used the services given Amazon Web Services due to their leadership and experience in cloud computing providing security, scalability, backup service and feasibility for the users.